2020
DOI: 10.3390/ijms21114188
|View full text |Cite
|
Sign up to set email alerts
|

A Proline Derivative-Enriched Fraction from Sideroxylon obtusifolium Protects the Hippocampus from Intracerebroventricular Pilocarpine-Induced Injury Associated with Status Epilepticus in Mice

Abstract: The N-methyl-(2S,4R)-trans-4-hydroxy-l-proline-enriched fraction (NMP) from Sideroxylon obtusifolium was evaluated as a neuroprotective agent in the intracerebroventricular (icv) pilocarpine (Pilo) model. To this aim, male mice were subdivided into sham (SO, vehicle), Pilo (300 µg/1 µL icv, followed by the vehicle per os, po) and NMP-treated groups (Pilo 300 µg/1 µL icv, followed by 100 or 200 mg/kg po). The treatments started one day after the Pilo injection and continued for 15 days. The effects of NMP were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…1 H NMR was used to detect the presence of NMP just for the water fraction to yield 1.43 g of pure NMP (14.3%). This yield is in agreement with a previous finding by qNMR ( 13 ). The NMP spectrum extracted from the fraction corresponded to the pure isolated compound N -methyl-(2S,4R)- trans -4-hydroxy-L-proline (Supplementary Figures S1 and S2).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1 H NMR was used to detect the presence of NMP just for the water fraction to yield 1.43 g of pure NMP (14.3%). This yield is in agreement with a previous finding by qNMR ( 13 ). The NMP spectrum extracted from the fraction corresponded to the pure isolated compound N -methyl-(2S,4R)- trans -4-hydroxy-L-proline (Supplementary Figures S1 and S2).…”
Section: Resultssupporting
confidence: 93%
“…After lyophilization or rotary evaporation of the solvent, the fractions yielded 3.13, 3.03, 2.03, and 1.84 g, respectively. By 1 H NMR, the presence of NMP was investigated and fractions were adsorbed on 20 g of silica gel for flash chromatography and then eluted with 10% CH 2 Cl 2 /MeOH (5 fractions of 50 mL), followed by 20% CH 2 Cl 2 /MeOH (9 fractions of 50 mL and 6 fractions of 100 mL) ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…These results are relevant in view of our recent report of the NMP anticonvulsant action in the intracerebroventricular pilocarpine model in mice (12). In that study, NMP was reported to decrease the pilocarpine-induced neuronal death and overexpression of GFAP and Iba-1 in hippocampal subfields.…”
Section: Discussionsupporting
confidence: 57%
“…Recently ( 11 , 12 ), we showed that the methanol fraction isolated from Sideroxylon obtusifolium leaves presents a high content of the anticonvulsant bioactive component N -methyl-(2S,4R)- trans -4-hydroxy-L-proline (NMP). This NMP fraction was shown to increase GFAP and Iba-1 expressions, biomarkers of astrocytes and microglia, in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Most bioactive small molecules, such as NMP, are known to interact with proteins or other macromolecule targets, which results in their final biological effects. Recently, we reported that one of the possible targets for the NMP molecule is the GABA transporter (GAT-1) [40]. These results point again to GABA neurotransmission involvement in the NMP action mechanism.…”
Section: Discussionmentioning
confidence: 79%